Eco-friendly waste plastic-based mortar incorporating industrial waste powders: Interpretable models for flexural strength - Jia, Huina; Li, Yali; AlAteah, Ali H.; Alsubeai, Ali; Alinsaif, Sadiq; Murtaza, Haseeb (Reviews on advanced materials science, 2025)
Glass powder, silica fume, and marble powder (MP) were investigated for their potential as sustainable additives to enhance mechanical properties, reduce environmental impact, and improve resource utilization in mortar formulations. This study utilized gene expression programming (GEP) and multi-expression programming (MEP) with experimental data to develop flexural strength models using these materials as eco-friendly mortar cement substitutes. The models were evaluated using ² values, statistical tests, sensitivity analysis, partial dependence plots (PDPs), Taylor’s diagram generation, and test and predicted results. The statistical measures demonstrated that MEP was the more accurate model compared to GEP. The sensitivity study revealed that plastic and sand had the most significant influence on flexural strength prediction, emphasizing the importance of their proportions in the mixture. PDPs further showed that cement, silica fume, and MP positively impact flexural strength, while sand and plastic exhibit optimal levels for enhanced performance. The study also highlighted the particle interaction sensitivity of glass powder, underlining the importance of mix design optimization to achieve improved mechanical behavior. The findings support the use of equation-based modeling and sustainable industrial byproducts to optimize mortar formulations, contributing to greener construction practices and reduced dependence on conventional cement.